Electrocardiographic Predictors of Adverse Outcomes Among Hospitalized COVID-19 Patients - Hershenson, Roy; Mahamid, Mostafa; Arow, Ziad; Hazan, Noah; Assali, Abid; Gabarin, Mustafa (International Journal of Innovative Research in Medical Science, 2022)
Background: There is growing evidence of cardiac injury in COVID-19. Minor studies examine electrocardiographic alterations at admission and during hospitalization are associated with major events and infection severity. Some reports that specific experimental therapies might cause QTc prolongation in COVID-19 patients may predispose them to arrhythmic complications. Objectives: to evaluate the relationship between electrocardiogram parameters and clinical outcomes of death, duration of hospitalization, and mechanical ventilation among patients hospitalized due to COVID-19 infection. Methods: The study included all verified COVID-19 patients hospitalized in a dedicated ward between March 2020 and March 2021. Inclusion criteria were the availability of admission-electrocardiogram and sufficient clinical data. In-hospital mortality, duration of hospitalization, and mechanical ventilation were defined as dependent indicators of major adverse events. ECGs were imported using a high-resolution scanner, and intervals were measured in a blinded manner using an on-screen digital calliper. The ECG parameters were computed with a designated algorithm from the bipolar and unipolar limb leads. Average RR interval, a standard deviation of normal-to-normal R-R intervals (SDNN), root mean square of successive differences between normal heartbeats (RMSSD), average QT, QT-peak, Tpeak-end, QTc, Tp-end/QT, and QRS durations were computed. Bivariate regression analyses between ECG parameters and clinical data were estimated with the Pearson correlation coefficient (r). Results: The cohort included 280 patients, of whom 100 had ECG results. Twenty included patients died in the hospital. Significant positive correlations were found between mortality and mean QRS. None of the other parameters reached statistical significance. Conclusions: High admission values of ECG-derived 10-sec QRS durations are associated with a high mortality rate in COVID-19 patients. Further prospective large-scale trials should be performed to corroborate these results and determine the role of other clinical modifiers.